Turk Arch Pediatrics 2022
DOI: 10.5152/turkarchpediatr.2022.22046
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine – a Boon to Parents of Children with Health Care Needs During COVID-19 Pandemic: A Qualitative Study from India

Abstract: Objective: The coronavirus disease 2019 pandemic had greatly impacted health worldwide. The nationwide lockdown was imposed to contain the virus transmission, which indirectly affected health care utilization. Pediatric patients’, as they are considered as a vulnerable group, parents faced a significant challenge to manage their children’s surgical and medical care needs during the coronavirus disease 2019 pandemic. The study aims to explore the parental approach to health care facilities to meet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Currently, increasing interest of families in digital media resources such as mobile applications, online videos, interventions from patient portals and podcasts, and their turn to and satisfaction with virtual environments in behavioral interventions, especially due to the pandemic, supports this hypothesis. 35 , 36 The results of a systematic review study conducted on this subject showed that technology-based programs focusing on the socioemotional development of children in low- and middle-income countries have promising effects on parenting. 37 Especially due to the pandemic the interest of families in digital media resources such as mobile applications, online videos, interventions from patient portals and podcasts, and satisfaction with virtual environments in behavioral interventions have increased.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increasing interest of families in digital media resources such as mobile applications, online videos, interventions from patient portals and podcasts, and their turn to and satisfaction with virtual environments in behavioral interventions, especially due to the pandemic, supports this hypothesis. 35 , 36 The results of a systematic review study conducted on this subject showed that technology-based programs focusing on the socioemotional development of children in low- and middle-income countries have promising effects on parenting. 37 Especially due to the pandemic the interest of families in digital media resources such as mobile applications, online videos, interventions from patient portals and podcasts, and satisfaction with virtual environments in behavioral interventions have increased.…”
Section: Discussionmentioning
confidence: 99%